Microbubble size control effect of pH, frother type, and dosage - Canezal, Edwin Roven T. (College of Engineering, University of the Philippines Diliman, 2015)
The aim of this study is to investigate the effects of pH, frother type, and dosage on controlling microbubble size. Common flotation frothers such as glycol ether, methyl isobutyl carbinol, and pine oil were used while pH conditions were set to 3, 7, and 11. On the other hand, frother dosages varied from 10 parts per million (ppm) to 250 ppm. The effects on surface tension and bubble size were determined using the aforementioned parameters. Bubbles were generated in frother solutions contained in a clear acrylic container by passing air through a porous ceramic disk (0.3 μm nominal pore size). Bubbles that have attached to the sampling section of the acrylic were the only ones documented using a USB digital microscope. Image analysis was then utilized to process images and to determine bubble size and size distribution. Meanwhile, surface tension measurements were done via the capillary rise method. The experimental tests revealed frother dosage has a significant effect on surface tension values of solutions. All frothers lowered surface tension but with varying degree. In contrast, pH had minimal effect on surface tension. For bubble size, it was observed that it is strongly affected by both frother dosage and pH. It was observed that the degree of bubble size reduction depends on frother type. However, beyond a dosage known as the critical coalescence concentration (CCC), bubble size is almost constant. The CCC of frothers at pH 7 and 11 was estimated below 100 ppm while that at pH 3 it is above 100 ppm. In summary, it was observed that bubble size is related to surface tension for some frothers employed. However, size was more likely influenced by the tendency of bubbles to coalesce as dictated by pH and frother dosage. To control bubble size, pH and frother dosage must therefore be adjusted taking into account the observation that low levels of the said factors favour coalescence leading to larger bubbles.